Sending and receiving: immunity sought by diplomats committing criminal offences - Moutzouris, Maria (Rhodes University, Faculty of Law, Law, 2009)
Diplomatic immunity is one of the oldest elements of foreign relations, dating back as far as Ancient Greece and Rome. Today, it is a principle that has been codified into the Vienna Convention on Diplomatic Relations regulating past customs and practices. Consuls and international organizations, although their privileges and immunities are similar to diplomatic personnel, do differ and are regulated by the Vienna Convention on Consular Relations and the United Nations International Immunities respectively. These Conventions have been influenced by past practices and by three theories during different era's namely exterritoriality, personal representation and functional necessity. The Vienna Convention on Diplomatic Relations further provides certain immunities and privileges to different levels of diplomatic officials, their staff and families. Privileges and immunities will be considered under various main categories, namely the diplomatic mission, the diplomatic official, diplomatic staff, and families. Each category receives privileges and immunities, for example immunities enjoyed by the diplomatic mission include mission correspondence and bags. Diplomatic officials enjoy personal inviolability, immunity from jurisdiction and inviolability of diplomats' residences and property. The staff and families of diplomatic officials too enjoy privileges and immunities. The problem of so many people receiving privileges and immunities is that there is a high likelihood of abuse. Abuses that arise are various crimes committed by diplomats, their staff and families. They are immune from local punishment and appear to be above the local law. Although the Vienna Convention on Diplomatic Relations provides remedies against diplomats, staff and families who abuse their position, it gives the impression that it is not enough. Various Acts in the United Kingdom, United States and the Republic of South Africa will be analysed in order to ascertain what governments have done to try and curb diplomatic abuses. Each will be considered and found that although they have restricted immunity from previous practices it still places the diplomats' needs above its own citizens. Thus several suggestions have been put forward and argued whether they are successful in restricting immunity comprehensively. Such suggestions are amending the Vienna Convention on Diplomatic Relations; using the functional necessity theory to further limit immunity; forming bilateral treaties between States as a possible means to restrict or limit; and lastly establishing a Permanent International Diplomatic Criminal Court. The key question to be answered is whether diplomatic immunity is needed for the efficient functioning of foreign relations between States.
Keywords: Diplomatic privileges and immunities; International crimes; Criminal law; International law